2010
DOI: 10.3354/meps08733
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem change in a South African marine reserve (1960–2009): role of seagrass loss and anthropogenic disturbance

Abstract: Seagrass ecosystems are disappearing throughout the world, raising several concerns for ecosystem functioning and biodiversity. In the present study we document changes in intertidal sandflat ecosystems over the last 5 decades in Langebaan Lagoon, a marine reserve on the west coast of South Africa, following large-scale losses of seagrass Zostera capensis. Aerial photography and GIS revealed a 38% loss of seagrass at sites in Langebaan Lagoon between 1960 and 2007. Longterm monitoring of one particular site, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…Insofar as the smaller members of the fauna at the upper levels of the Nanozostera beds are concerned, and except in the vicinity of the large pits excavated in the sediment, at least the Knysna system appears to be resilient to current bait-digging levels. It has also provedthus far -to have escaped loss of seagrass on the scale that has afflicted Langebaan over the last 50 years (Pillay et al, 2010a), the losses in the Outer Basin referred to in the Introduction having been almost completely offset by gains in the Middle Basin (CES, 2009), and thus its importance as a habitat for seagrass in southern Africa cannot be overestimated. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insofar as the smaller members of the fauna at the upper levels of the Nanozostera beds are concerned, and except in the vicinity of the large pits excavated in the sediment, at least the Knysna system appears to be resilient to current bait-digging levels. It has also provedthus far -to have escaped loss of seagrass on the scale that has afflicted Langebaan over the last 50 years (Pillay et al, 2010a), the losses in the Outer Basin referred to in the Introduction having been almost completely offset by gains in the Middle Basin (CES, 2009), and thus its importance as a habitat for seagrass in southern Africa cannot be overestimated. …”
Section: Discussionmentioning
confidence: 99%
“…Species such as Hydrobia knysnaensis and 'Rissoa' capensis 1 were abundant in both Nanozostera and associated areas of bare sediment located within blocks of marsh but scarce or absent from fronting eelgrass beds along the lagoon shore. Besides being of considerable ecological interest in respect of the processes structuring assemblages of species, such spatial variation in the fauna of seagrass beds has very clear implications for strategies to conserve their organismal diversity and rare species (McNeill and Fairweather, 1993;Butler and Jernkoff, 1999;Green and Short, 2003;Larkum et al, 2006); something of particular importance at a time of worldwide seagrass decline (Duarte, 2002;Orth et al, 2006;Duarte et al, 2008;Hughes et al, 2009;Pillay et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Most species of aquatic invertebrates feed by filtering or ingesting nutrients from the water or sediment, and thus can accumulate high concentrations of toxicants or contaminants that may be present within a habitat. It has been observed that population disruption or loss of bottom-level organisms and benthic invertebrate species can result in the disruption and even collapse of entire ecosystems (Owens & Dittman, 2003;Pillay et al, 2010;Wallace & Webster, 1996).…”
Section: Case Study: Melita Plumulosa the Environmental Canary Of Eamentioning
confidence: 99%
“…Both studies also indicate that this species has been underrated in terms of its ability to structure benthic marine communities. The present study is also motivated by the fact that P. exigua occurs almost exclusively in and around seagrass (Zostera capensis) beds in Langebaan Lagoon and that the abundance of both species has been declining in the system (Pillay et al 2010b). This experiment is therefore important in understanding the consequences of further losses of this starfish for intertidal sandflats in Langebaan Lagoon.…”
mentioning
confidence: 99%